Highly flexible mechanical energy harvester based on nylon 11 ferroelectric nanocomposites - Ram, Farsa; Radhakrishnan, Sithara; Ambone, Tushar; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2019)
We report here a flexible piezoelectric energy harvester using castor-oil-derived nylon 11 and biomass-derived cellulose nanocrystals (CNC). Using a simple solution casting process, we were able to fabricate flexible large area nylon 11 and composite films. Neat nylon 11 films crystallized predominantly in the α- phase. Incorporation of CNC at a low concentration of 2–5 wt % resulted in almost complete transition of α-phase to polar γ-phase, which could be attributed to strong hydrogen bonding interactions between CNC and amide groups in nylon 11. This remarkable shift in crystallization behavior also led to enhanced piezoelectric performance. We also found that the addition of 5 wt % glycerol (on the dry weight of nylon 11 or composite) enhanced the flexibility of the film. Energy harvesting devices made from 5 wt % nylon 11/CNC films showed about 2.6 times higher output voltage as compared to neat nylon 11 devices under similar impact conditions, and the effect was durable over 800 cycles. These devices were also used to charge a 10 μF polarized capacitor, and we found that the 5 wt % nylon 11/CNC devices charged up to 3.78 V in 90 s, which is 2.8 times higher than nylon 11 devices. To the best of our knowledge, this is the first report on nylon 11 nanocomposites, where cellulose nanocrystals have been used to enhance the electroactive γ phase in nylon 11 and yield such high piezoelectric performance.